Updated phylogenetic and systematics of the Acrapex albivena Hampson, 1910 and A. stygiata (Hampson, 1910) species groups (Lepidoptera, Noctuidae, Noctuinae, Apameini, Sesamiina), with the description of nine new species from the Afrotropics. Issue 3 (4th May 2019) - Le Ru, Bruno; Musyoka, Boaz K.; Capdevielle-Dulac, Claire; Pallangyo, Beatrice; Njaku, Mohamedi; Goftishu, Muluken; Assefa, Yoseph; Chipabika, Gilson; Conlong, Desmong; Ong'Amo, George; Barbut, Jérôme; Kergoat, Gael J.
Summary: The genus Acrapex Hampson, 1891 (Lepidoptera, Noctuidae, Noctuinae, Apameini, Sesamiina) constitutes a speciose group of noctuid stemborers mostly distributed in the Afrotropics. In this study nine new Acrapex species are described: Acrapex abyssinica n. sp ., Acrapex dabaga n. sp ., Acrapex jansei n. sp ., Acrapex kifanya n. sp ., Acrapex lusinga n. sp ., Acrapex ngwenya n. sp ., Acrapex njombea n. sp ., Acrapex vetiveria n. sp . and Acrapex zima n. sp . All species are assigned to the A. albivena group with the exception of A. lusinga which is assigned to the A. stygiata group. We also provide supplemental descriptions for two previously described species of the A. albivena group, A. punctosa Berio, 1973 and A. sysciodes, Berio, 1973, and for one species belonging to the A. stygiata group: A. brunneella Le Ru, 2014. Host plants of three species are recorded; A. brunneella and Acrapex jansei were reared on Cymbopogon pospischilii (K. Schum.) C. E. Hubb and A. vetiveria on Chrysopogon zizanioides (L.). We also conducted molecular phylogenetic analyses (using both Bayesian inference and maximum likelihood) on a multi-marker (four mitochondrial and two nuclear genes) molecular dataset encompassing 138 specimens (including 98 specimens from the A. albivena group and 23 specimens from the A. stygiata group) from 48 stemborer species. The results of the corresponding analyses support the monophyly of the two groups of interest and the species status of all newly described taxa, except for A. lusinga that was not sequenced. The phylogenetic analyses also unravel several evolutionary lineages whose precise status is pending because their DNA was extracted from larval stages.